Corporate Secretary's Manual and Guide (Book). - Cannon, Arthur M.; Burnham, Walter C. (The Accounting Review, 1950)
Reviews the book "Corporate Secretary's Manual and Guide," by Lillian Doris and Edith J. Friedman.